ANALISIS POTENSI EKONOMI SEKTORAL KORIDOR UTARA SELATAN PROPINSI JAWA TIMUR TAHUN 2005 – 2009 - M. Sofyan Andiatma (Jurnal Ekonomi Pembangunan, 2014)
The research analyzes main sector, contribution of each sector and economic growth pattern in Regency / City North-South Corridor of East Java Province year 2005-2009. Research method used is Location Quentiont (LQ) analysis, contribution analysis, and Klassen typology analysis. The research uses Location Quentiont (LQ) analysis tool which is sector with the largest superiority, which are electricity, gas, and clean water in Gresik regency and sector with the smallest superiority which are farm, mining, and excavation in Mojokerto City, according to contribution analysis of trading, hotel, and restaurant in Batu city gave the biggest contribution, which is 51.72% according to Klassen typology analysis of Regency / city with fast and growth economic development is Surabaya and Mojokerto. Rapid development is Pasuruan regency, Blitar regency, batu city, Pasuruan, Blitar. Developed and pressed are Gresik regency, Sidoarjo regency, andMalangCity. The one with left economic growth are Mojokerto regency andMalangregency. According to the analysis done, it needs role from all communities, especially government to pay attention, montitor, and develop all main potential in Regency / City in North-South Corridor of East Java.